Bibliometric Analysis of Sports Management: Integrating Event Management, Marketing, Finance, and Policy Trends - Bachtiar, Ishak; Akhmad, Noor; Gumilang, Eva Sri (LITPAM, 2026)
The rapid transformation of the global sports industry, driven by digitalization, globalization, sustainability demands, and increasingly complex governance structures, has created a need for a more integrated understanding of sports management research. Although event management, marketing, finance, and policy have each received scholarly attention, studies that map their interconnections within a comprehensive research framework remain limited. This study aims to examine the development of sports management literature and identify publication patterns, dominant contributors, and emerging thematic trends. A quantitative bibliometric approach was employed using publication data from the Web of Science database covering the period from 1982 to 2025. The analysis focused on publication growth, country contributions, author and institutional productivity, journal and publisher distribution, and keyword relationships. The findings show that sports management research has expanded notably after 2020, with contributions dominated by developed countries while emerging participation from developing countries has begun to appear. The keyword mapping further reveals increasing attention to sustainability, digitalization, strategic management, sports marketing, sports entrepreneurship, higher education, and charity sport events. These findings indicate that sports management is evolving into a multidisciplinary field that requires a holistic framework integrating managerial, financial, policy, technological, and sustainability perspectives. Future research should strengthen comparative and empirical studies, particularly in developing-country contexts. Transformasi pesat industri olahraga global, yang didorong oleh digitalisasi, globalisasi, tuntutan keberlanjutan, dan struktur tata kelola yang semakin kompleks, telah menciptakan kebutuhan akan pemahaman yang lebih terintegrasi mengenai penelitian manajemen olahraga. Meskipun manajemen acara, pemasaran, keuangan, dan kebijakan masing-masing mendapat perhatian ilmiah, penelitian yang memetakan keterhubungannya dalam kerangka penelitian yang komprehensif masih terbatas. Penelitian ini bertujuan untuk mengkaji perkembangan literatur manajemen olahraga dan mengidentifikasi pola publikasi, kontributor dominan, dan tren tematik yang muncul. Pendekatan bibliometrik kuantitatif digunakan dengan menggunakan data publikasi dari database Web of Science yang mencakup periode 1982 hingga 2025. Analisis ini berfokus pada pertumbuhan publikasi, kontribusi negara, produktivitas penulis dan institusi, distribusi jurnal dan penerbit, dan hubungan kata kunci. Temuan menunjukkan bahwa penelitian manajemen olahraga telah berkembang pesat setelah tahun 2020, dengan kontribusi didominasi oleh negara-negara maju sementara partisipasi dari negara-negara berkembang mulai terlihat. Pemetaan kata kunci lebih lanjut mengungkapkan peningkatan perhatian terhadap keberlanjutan, digitalisasi, manajemen strategis, pemasaran olahraga, kewirausahaan olahraga, pendidikan tinggi, dan acara olahraga amal. Temuan ini menunjukkan bahwa manajemen olahraga berkembang menjadi bidang multidisiplin yang memerlukan kerangka holistik yang mengintegrasikan perspektif manajerial, keuangan, kebijakan, teknologi, dan keberlanjutan. Penelitian di masa depan harus memperkuat studi komparatif dan empiris, khususnya dalam konteks negara berkembang.